Exploring the Effectiveness of Remedial Programs and Technology in Overcoming Learning Barriers in Secondary Education - Wahid Zaini, Abdul; Al Mursyidin, Rahmatul Aziz; A’lal Hikam, Muhamad (International Journal of Instructional Technology, 2024)
This study explores the impact of remediation programs and technology integration on addressing learning difficulties among secondary school students. With the rise of digital tools and innovative teaching strategies, many students continue to face significant academic challenges, particularly in subjects like mathematics, English, and physics. This research aims to assess how combining these educational innovations influences student motivation, comprehension, and academic performance. Utilizing a case study approach, the research was conducted at MA LUBBUL LABIB Probolinggo, a secondary school that has implemented both remediation programs and technology-based learning strategies. Data collection methods included participatory observation, in-depth interviews with students, teachers, and administrators, and document analysis of academic performance and teaching materials. The study found that students who participated in the remediation program reported increased confidence, motivation, and improved academic outcomes. Furthermore, the integration of technology was shown to enhance student engagement by facilitating independent learning and immediate feedback. These findings suggest that a combined approach of remediation and technology can effectively address learning difficulties, particularly in diverse educational settings. This research contributes to a deeper understanding of how educational innovations can be implemented to improve student success and provides valuable insights for educators and policymakers aiming to enhance the learning experience in secondary education.